Analisis Kinerja Keuangan Perbankan Syariah Indonesia Sebelum dan Sesudah Merger Bank Syariah Indonesia - Shaima Asifaul Afnani; Dedi Suselo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research is motivated by the measurement of financial performance in Islamic banking. The existence of financial performance in Islamic banking will affect the good value for the banking company, because it will become a reference for investors and become a reference in how much the value of the stock price will be determined by investors. This study aims to analyze the existence of financial performance in Islamic banking in Indonesia before and after the merger. The data in this study were obtained and obtained from the financial reports of Islamic banking in Indonesia. This study uses secondary data by taking data sources on the internet. The method of data analysis used is comparative analysis. The results of this study provide an indication that there are significant differences between profitability, liquidity, solvency, activity ratios, and market ratios before and after the merger to become Bank Syariah Indonesia, with the merger making Bank Syariah Indonesia experience rapidly increasing revenues. This means that Working Capital has a significantly positive influence on the results of operations at Bank Syariah Indonesia.